1977
DOI: 10.1021/es60128a006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide photolysis in the Los Angeles atmosphere

Abstract: Atmospheric measurements of k\, the rate of NO2 photolysis, were made in El Monte, Calif., by use of a tubular quartz reactor to measure directly the conversion of NO2 to NO in an N2 atmosphere. A least-squares treatment of the data from September 1975 resulted in the following empirical relationships for predicting k j from standard UV radiometric data. 0°< Solar zenith angle < 40°:(min-1) = 0.079 (1/cos z) + 0.002 X radiometric UV (mW/cm2); 40°< solar zenith angle < 90°: k\ (min-1) = 0.16 (1 -cos z) + 0.088 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 1 publication
0
55
0
Order By: Relevance
“…(1977). A spherical reactor of the type used by Sickles and Jeffries (1975) and a cylindrical (plug flow) reactor were examined (Zafonte et al, 1977). They found the j value measured in the spherical cell to be flow dependent, yielding higher j values at higher flow rates, while the j values in the cylindrical cell were independent of flow rate.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1977). A spherical reactor of the type used by Sickles and Jeffries (1975) and a cylindrical (plug flow) reactor were examined (Zafonte et al, 1977). They found the j value measured in the spherical cell to be flow dependent, yielding higher j values at higher flow rates, while the j values in the cylindrical cell were independent of flow rate.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Thus, no transmission correction factor need be applied when the reactor is infinite in length, or where there is no inlet/outlet system, since the internally reflected light ray will exactly compensate for the reflected light lost initially (Zafonte et al, 1977). An 'end correction' can be made for a finite tubular reactor, which is proportional to the area of the endcaps and inversely proportional to a function of photolysis cell length.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of reflection in the double quartz cylinder was determined by ray-tracing, using an approach similar to that used by Zafonte et al (1977) for a single wall, infInitely long, cylinder. For an infInitely long, non-absorbing, double-walled cell the reflection losses are also compensated by multiple internal reflections for all angles of incidence (Madronich, 1982).…”
Section: S Optical Considerationsmentioning
confidence: 99%
“…with those of Zafonte et al (1977). The correlation curve given by Harvey et al (1977) is shown in Figure 8 for comparison.…”
Section: Comparison Ofj No With Eppley Measurementsmentioning
confidence: 99%